Murine liver repair via transient activation of regenerative pathways in hepatocytes using lipid nanoparticle-complexed nucleoside-modified mRNA - Fatima Rizvi (Nature Portfolio, 2021)
When severely or chronically injured, the liver loses ability to regenerate. Here, the authors utilize transient lipid nanoparticle-enclosed HGF and EGF-encoding mRNA delivery to induce hepatocyte proliferation and harness recovery of liver function in murine acute and chronic liver injury models.